Structure, optical and electrical properties of ITO films on flexible polyimide substyrates - Khrypunov, G.S. (Functional Materials, 2004)
ITO layers on industrial polyimide films intended for high efficiency flexible CdTe solar cells have been obtained for the first time. The air-annealed ITO films obtained at the magnetron power of 1500 mW/cm2, oxygen partial pressure in the argon/oxygen mixture 3 % (vol.), and the deposition temperature 450°C show the surface resistance of 11 Ohm/D. In the photosensitivity region of the CdS/CdTe solar cells, the average transmission coefficient of the ITO/polyimide system has been found to be 72 %. Впервые на промышленных полиамидных пленках получены слои ITO для высокоэффективных гибких солнечных элементов на основе CdTe. После изготовления солнечного элемента, пленки ITO, полученные при мощности магнетрона 1500 мВт/см2, парциальном давлении кислорода в составе аргоно-кислородной смеси 3 об.% и температуре осаждения 450°С, имеют величину поверхностного электро-сопротивления 11 Ом/D. В области фоточувствительности солнечных элементов CdS/CdTe средний коэффициент пропускания гетеросистем ITO/polyimide составлял 72 %. Вперше на промислових полiамiдних плiвках отримані шари ITO для високоефективних гнучких солнячних єлємєнтів на основі CdTe. Після виготовлення сонячного елемента плівки ITO, що отримані при потужності магнетрона 1500 мВт/см2, парциальному тиску кисню в складі аргоно-кислородной суміші 3 об.% і температурі осадження 450°С, мають поверхневий опір 11 Ом/D. У області фоточутливості сонячних елементів середній коефіцієнт пропускання гетеросистем ITO/polyimide складав 72 %.